Trauma, healing and community in Toni Morrison's Beloved and Home - Marina de Almeida Pedrosa (2019)
This dissertation examines Toni Morrisons Beloved and Home from the perspective of trauma studies. I argue that the experience of slavery acts upon the characters in a way that leaves them mentally deranged and physically vulnerable even when they have not faced bondage directly. Besides individual trauma there is also cultural trauma that affects the protagonists lives and relations, perpetuating the unspeakable pains of severe emotional and mental distress through generations. This dissertation takes a close look at what happens psychologically to an individual when one is traumatized and how the protagonists achieve healing through the community of women. This approach mainly draws on Gabriele Schwabs discussion about how violent legacies are difficult to recount or even to remember because usually one represses or buries these contents in an unreachable psychic crypt. A person who refuses to mourn a loss by disavowing it, keeps it inside by burying it in a psychic tomb. Although appearing to be dead, this loss is psychically alive and returns as a ghost to haunt the victim. Flashbacks, nightmares and compulsive repetitions are some of the consequences of this seemingly alien force that makes these intrusive memories somehow unbearable and, therefore, unspeakable. In this sense, this research discloses how discourse is affected by the traumatic experience. I also regard the way characters find atonement by finally breaking the crypt, having access to their history and putting it into words by telling their story. I conclude that this dissertation moves beyond in the study of trauma literature, for it shows that mourning over individual and collective trauma allows healing to take place in both works through the community of women, enabling the characters to reconsider the wounds of a shameful past in manners that can exorcize the ghosts of trauma.